Profil Kelompok Tani Makmur Abadi dalam Pengembangan Wisata Petik Apel - Muhammad Shivana R; Hardika Hardika; Ahmad Mutadzakir (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2016)
Abstract: Profile of Farmers Group of Makmur Abadi in Tourism Development of Picking Apples. Makmur Abadi farmers group in is the embodiment of a container that is required of farmer’s, farmer’s groups develop tourism pick apples, many of which have not been revealed how organizing patterns that exist in Makmur Abadi farmer groups in developing tourism. This study aims to describe the pattern of organizing in Makmur Abadi farmer group in developing tours include: the Division of labor, the pattern of leadership, how to increase active members. This research used the qualitative case study research.Abstrak: Profil Kelompok Tani Makmur Abadi dalam Pengembangan Wisata Petik Apel. Kelompok Tani Makmur Abadi adalah perwujudan dari sebuah wadah yang diperlukan para petani, kelompok tani ini mengembangkan wisata petik apel, banyak yang belum terungkap bagaimana pola pengorganisasian yang ada di Kelompok Tani Makmur Abadi dalam mengembangkan wisata. Penelitian ini bertujuan untuk mendeskripsikan pola pengorganisasian di Kelompok Tani Makmur Abadi dalam mengembangkan wisata meliputi: pembagian kerja, pola kepemimpinan, cara peningkatan keaktifan anggota. Penelitian ini menggunakan penelitian kualitatif studi kasus.